Effects of Tip Injection on a Turbofan Engine with Non-Invasive High-Speed Actuators - Yannik Schäfer; Marcel Stößel; Arnaud Barnique; Dragan Kožulović (International Journal of Turbomachinery, Propulsion and Power)
This paper presents an analysis of the stability margin improvement (SMI), which is also known as stall margin improvement, achieved by continuous tip air injection. New piezoelectric actuators were designed and manufactured with a new engine inlet for the Larzac 04 C5 jet engine. It has noninvasive injection positions that do not have any measurable effect on the inlet air flow when it is switched off. The main focus of the system design was to achieve high power of the injected air and, as a result, a high SMI. The results presented enable a maximum SMI of 99%. A variety of engine operating conditions and injection positions were experimentally tested and discussed regarding SMI. Additionally, the complex relationship between SMI gains and thrust specific fuel consumption (TSFC) is explored in a power balance analysis, revealing a trade-off between SMI improvement and increased energy consumption.